2022
DOI: 10.1021/acs.orglett.1c03920
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of Nitropyridines via Vicarious Nucleophilic Substitution

Abstract: Electrophilic nitropyridines react with sulfonyl-stabilized carbanions to give products of C–H alkylation via vicarious nucleophilic substitution. The process consists of formation of the Meisenheimer-type adduct followed by base-induced β-elimination of the sulfinic acid (e.g., PhSO 2 H). Mechanistic studies reveal that in the latter step alkyl substituent and adjacent nitro group tend to planarize for effective stabilization of benzyl anion, and thus, adduct of hindered isopropyl carba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Interestingly, presence of acceptor groups at the aryl rings of the sulfones (3,5‐Cl 2 , 3,5‐(CF 3 ) 2 ), at the alcohol fragment of the sulfonate (trifluoroethanol derivative), and as ancillary groups of the sulfonium salt (phenyl rings), caused decrease of yields of the alkylated product 5 a . The data confirmed that for this class of substrates, those giving best results were already employed for alkylation of pyridine derivatives, [10] and further improvement of the reaction course seems to be unlikely.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Interestingly, presence of acceptor groups at the aryl rings of the sulfones (3,5‐Cl 2 , 3,5‐(CF 3 ) 2 ), at the alcohol fragment of the sulfonate (trifluoroethanol derivative), and as ancillary groups of the sulfonium salt (phenyl rings), caused decrease of yields of the alkylated product 5 a . The data confirmed that for this class of substrates, those giving best results were already employed for alkylation of pyridine derivatives, [10] and further improvement of the reaction course seems to be unlikely.…”
Section: Resultssupporting
confidence: 76%
“…After elimination of the first possibility, we focused on distinction between adduct epimerization and syn ‐elimination scenarios. To gain more insights into the reaction mechanism deuterated substrates 1 a and 3 d were tested under standard alkylation conditions, [10] with reaction time shortened to 10 min (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analogous yet less frequently encountered transformation is the nucleophilic aromatic substitution of hydrogen (S N H), in which a nucleophile substitutes for a hydrogen atom on a nitro­(hetero)­arene . The intermediate σ H adduct can be converted to the product by vicarious nucleophilic substitution (VNS) if the nucleophile possesses a leaving group positioned such that an elimination step is possible (Scheme B). , In the absence of a leaving group, the σ H adduct can oxidatively rearomatize to complete the process known as the oxidative nucleophilic substitution of hydrogen [ONSH (Scheme C)]. At present, there are several hypotheses for the mechanism of oxidation, but conclusive experiments are lacking.…”
mentioning
confidence: 99%
“…Our research group explores organic transformations of sulfonyl- and carbonyl-containing substrates, demonstrated on functionalization of nitroarenes, 13 synthesis and transformations of sulfonyl fluorides, 14 and carbonyl olefination reactions. 15 Recently, we developed olefination with sulfonyl halides and esters , which mimics the Horner-Wadsworth-Emmons reaction of alkanephosphonates.…”
mentioning
confidence: 99%